Is suicide assessment harmful to participants? Findings from a randomized controlled trial. (16th April 2016) - Harris, Keith M.; Goh, Melissa Ting‐Ting
Abstract: There is considerable debate on whether suicide assessment carries an iatrogenic risk for participants/patients. A double‐blind randomized controlled trial (registration: R000022314) tested the emotional impact of suicide assessment on participants ( n =  259) randomly assigned to experimental ( n  = 122) or control conditions ( n  = 137). The experimental condition included the Suicidal Affect‐Behavior‐Cognition Scale and intensive death‐related questions, the control condition a quality of life scale. Both included measures of depression, social support and loneliness. Affective states were assessed immediately before and after testing, and research biases minimized. Post‐test debriefing interviews collected qualitative reactions. Experimental participants ranged from nonsuicidal to highly suicidal. Between‐groups ANCOVAs and repeated measures ANOVAs showed no differences by study condition, and no pre‐post‐test affect changes for either condition or suicidal participants ( P >  0 . 10), supporting the null hypothesis of no iatrogenic effects. However, depressive participants in both conditions showed significant decreases in positive affect ( P <  0 . 05). Smallest real difference (SRD) scores approximated clinically meaningful differences and showed 20% of participants had a significant positive survey reaction, 24% a negative reaction, with the rest neutral. Linear regressions revealed depressive symptoms and perceived family support, but not suicidality or other factors, predicted negative affect changes, which was supported by qualitative findings. Social desirability bias was also found in qualitative survey responses. No evidence of iatrogenic effects of suicide assessment were found. Recommendations are made to counter possible negative assessment effects on depressive participants/patients, and nurses and other caregivers are encouraged to talk to patients about suicidal symptoms.